What Predicts Out-of-Home Placement in Juvenile Court Dispositions? A Systematic Review and Meta-Analysis. - Zane, Steven N.; Pupo, Jhon A. (Journal of Youth & Adolescence, 2023)
Research suggests that juvenile court dispositions are influenced by legal factors, such as offense severity and prior record, as well as extralegal factors, such as race/ethnicity, sex, and age. To date, however, no research has reviewed whether legal or extralegal factors are more predictive of juvenile court dispositions across extant research. To address this gap, the present study reports on a systematic review and meta-analysis of predictors of residential placement in the juvenile justice system. A total of 40 independent samples were analyzed from 33 studies that met the criteria for inclusion in the review. Meta-analytic techniques were used to examine the average effects of offense characteristics, prior record, age, preadjudication detention status, race and ethnicity, sex, and contextual factors on odds of placement. The findings suggest that legal factors are more strongly associated with juvenile court dispositions than extralegal or contextual factors. Additionally, the strongest predictor of placement was whether the juvenile defendant had been detained at intake, illustrating the influential role of early case assessment in juvenile court.